2021
DOI: 10.1177/03915603211022942
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma of tunica vaginalis: Two extremely rare case reports

Abstract: Introduction: Malignant mesothelioma (MM) of tunica vaginalis is a very rare tumor and it has a poor prognosis. It is not easy to diagnose the disease preoperatively because there is a lack of comprehensive studies and information about the disease. We would like to present our two cases with severe scrotal edema and hydrocele, which were debrided perioperatively due to scrotal necrosis, followed by radical inguinal orchiectomy and subsequently diagnosed as MM of tunica vaginalis. Case 1: A 74-year-old male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The accurate diagnosis of MM of the spermatic cord is crucial but rarely achieved preoperatively, posing a challenge for patient management [12,13]. Most cases of MM of the spermatic cord are determined intraoperatively and present with papillary excrescences or fibrotic thickening of tunica vaginalis with or without hemorrhagic hydrocele fluid [8].…”
Section: Discussionmentioning
confidence: 99%
“…The accurate diagnosis of MM of the spermatic cord is crucial but rarely achieved preoperatively, posing a challenge for patient management [12,13]. Most cases of MM of the spermatic cord are determined intraoperatively and present with papillary excrescences or fibrotic thickening of tunica vaginalis with or without hemorrhagic hydrocele fluid [8].…”
Section: Discussionmentioning
confidence: 99%
“…Spiess et al ( 15 ) reported that 4 of 5 patients with mesothelioma had a history of asbestos exposure. A 10-fold increase in the risk of malignant mesothelioma has been reported among the immediate family members of patients with a history of asbestos exposure ( 16 ). In addition, conditions such as an old testicular injury, hiatal hernia and long-term syringomyelia may also be predisposing factors for the development of this disease ( 1 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most reported patients are over age 50, with median ages at diagnosis reported as 61, 62, or 72 3,9,10. The well-differentiated papillary type, in contrast, has occurred mostly in younger men11,12 with the exception of one 70-year-old 13. The oldest patient reported was age 90 14.…”
Section: Epidemiology and Preoperative Findingsmentioning
confidence: 99%
“…3,9,10 The well-differentiated papillary type, in contrast, has occurred mostly in younger men 11,12 with the exception of one 70-year-old. 13 The oldest patient reported was age 90. 14 The best-established risk factor for tunica vaginalis mesothelioma is asbestos exposure, present in 34% of the patients whose history was reported.…”
Section: Epidemiology and Preoperative Findingsmentioning
confidence: 99%